SCIENTIFIC BASIS OF WORKS CMA LUTSOPERATIONS IN INTERACTION WITH ROLLING STOCK AND MAKROLOGISTICS SYSTEM LINEANDCOMPLEXES - Полтавець, М. А.; Омельченко, О. Д. (Science-based technologies, 2016)
The paper examines the main directions of scientific progress aimed at electro saturationsystem, creating mechanized and automated production systems in current lines and complexes and improvement of production and labor, control production processes. Considered as organizationalandtechnologicalprerequisites automation of production processes involving the production and improving the transition from discrete to continuous technology optimization of production processes of storage and more. In work conditions that can lead to the introduction of automation by public micro automationindividual operations.